Educational Views on The Use of ChatGPT: Research was Conducted on Teachers - Umam, Khoirul; Ramadhani Putra, Ivan; Danial, Haris; Masum, Hadiansyah; Ulfa Sholihannisa, Lulu (Journal International Inspire Education Technology, 2024)
Artificial intelligence technology is growing rapidly in various fields, including education. One of the artificial intelligence technologies that can be utilized in learning is ChatGPT. ChatGPT can be used in schools to help students learn in a more interactive and interesting way. The purpose of this study was to determine the teachers' views on the use of ChatGPT in the learning process. The method used in this research is a qualitative method, data obtained through distributing questionnaires conducted online. The results of this study indicate that educational views on the use of ChatGPT are very influential on the learning process and increase the confidence of students. The conclusion of this study explains that the ability of ChatGPT artificial intelligence technology determines how active students are in learning. The limitation in this study is that researchers only conducted research on educational views on the use of ChatGPT: The research was conducted on teachers even though there are still many technologies that can be used as alternatives in improving student learning. Researchers hope that there will be similar studies that examine other learning. Researchers also recommend that this research can be used as a benchmark and make a reference for further research.